PENYALURAN ZAKAT FITRAH KEPADA DUKUN BERANAK DALAM TINJAUAN HUKUM ISLAM: (Studi Pada Masyarakat Dusun Rantau Panjang Kecamatan Sebangki Kabupaten Landak) - Setiawan, Dedi; Marluwi, Marluwi; Fadhil, Moh. (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This study aims to find out why the people of Dusun Rantau Panjang choose to distribute zakat fitrah to traditional birth attendants and to know about the delivery of zakat fitrah to traditional birth attendants according to Islamic law. This study uses a qualitative method (field research) empirical normative type. Sources of primary data through interviews and secondary data from previous studies. While the data analysis technique consists of data reduction, data presentation and conclusions. Then the validity of the data is checked by doing a member check. The results showed that the distribution of zakat fitrah in Dusun Rantau Panjang was distributed directly and through amil zakat. The distribution of zakat fitrah to traditional birth attendants is still not in accordance with Islamic law because the traditional birth attendant is still considered a capable person. Some people channel their zakat to traditional birth attendants because they do not know their legal status. The distribution of zakat fitrah for dukun beranak is not in accordance with the provisions in the Qur'an at-taubah verse 60. Traditional birth attendants tional midwife can receive zakat fitrah if they fall into one of the eight asnaf categories.